Influence of Stone Shape Factor on the Pull-Out Resistance of Geogrid in the Soil-Rock Mixture - Yongshuai Sun; Xuefeng Li; Guihe Wang (Advances in Materials Science and Engineering)
In this paper, the particle shape factor of the stone in the soil-rock mixture was used as the specific research object of the geogrid pull-out test, combining the random generation method and evaluation criteria of rock blocks in the soil-rock mixture, and a feasible method for classifying stones according to their shape factors is presented. By comparing the mechanical behavior of soil-rock mixture composed of rock blocks with different rock material shape factors in the geogrid pull-out tests under different working conditions, we studied its changing laws. The research shows that with the increase of the shape factor of the stone, the pull-out resistance of the geogrid gradually decreases. When the stone paved in the model box changes from a single layer to a double layer, the pull-out resistance of the geogrid increases, and there is a disturbance range in the contact interface between the geogrid and the stone; stone blocks 5 cm away from the geogrid surface can still have an indirect effect on the pull-out resistance of geogrids; the pull-out resistance of geogrid in clay is greater than that in the sand; and an empirical expression for predicting the pull-out resistance of geogrids is obtained. This empirical expression helps to explain the influence mechanism of stone shape on drawing resistance of geogrid.